THE ROLE OF ISLAMIC BOARDING SCHOOL AS SOCIALIZATION AGENT OF ECOLOGICAL VALUES (A CASE STUDY IN SAIFULLAH AN NAHDLIYAH ISLAMIC BOARDING SCHOOL) - Harahap, Ramadhan (Proceeding International Conference of Science Technology and Social Humanities, 2022)
There are many studies on Islamic Boarding School in Indonesia , but the study which associating with Islamic boarding school as socialization agent of ecological values is still rare. This study aims to examine the understanding and concepts regarding the environment in Islamic Boarding School and hoe the process of learning about religious values in the environment, also want to know the implementation of the learning. Data collection was done for first in-depth interviews to the Islamic Boarding School manager and the two primary data from the students (male and female). The study was found that: First, most the students perceived the concepts of the environment and agreed to cleanliness association as part of faith. Secondly, a little percentage of male or female students are resistant to the environmental concept and their studies are inseparable from the existence of patriarchal culture carried on the contextual conditions that enclosed it, therefor the way of thinking, behaving is much influenced by the conditions in where they live. Third, the learning process associated with keeping the environment socialized through some yellow book recitation, by outing class, artworks contest related to environmental hygiene and learning comfort, voluntary work. Fourth, most students was agree to work once a week and agree on the existence of punishment if not participate in voluntary work. Fifth, actions by students associated with violations (cleanliness work), most of them proposed a fine or punishments.